Two old broads ebook Stuff you need to know that you didn't know you needed to know. - Hecht, M. E. (2022)
Written by renowned surgeon and expert on the art of aging, Dr. M.E. Hecht, with her friend Whoopi Goldberg lending her unique point of view, Two Old Broads is laugh out loud funny and?tells it like it is for all of us who left middle age in the dust and want to be present, positive, and as extraordinary as ever in our golden years. Whoopi joins Dr. Hecht in a lively conversation about growing older with no apologies. Dr. Hecht, who passed away a few short months prior to publication, shares her 93 years of wisdom with Whoopi and their fellow "broads." Together, these two kindred spirits will help you: stay active physically and mentally make finalizing your will more rewarding than it sounds navigate tricky subjects, such as whether you need a home aide win friends and influence people or take a nap, depending on the day discover joy in relationships even when your excretions outweigh your secretions get up financially, physically, and emotionally after a fall keep a sense of humor about getting older (of course!) Imminently practical and?rooted firmly in the adage that getting older is not for sissies, Two Old Broads is the aging book for the ages. You've survived the past; why not embrace the present and prepare for the future so you thrive and find more time to laugh along the way?